A Relationship between Soft Skill and Caring of Nurse in a Hospital in Medan - Mazly Astuty; Dameria Ginting (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Caring is a nurse action to care someone else based on morality and humanity. Caring is influenced by soft skill that a nurse has. Soft skill is an ablility that someone has related to communication, adaptation and socialization. This cross sectional study was aimed to gain the relationship between soft skill and nurse caring. This study used a questionnaire that was given to one hundred and fifty one patients in inpatient ward. The result showed that most nurse soft skill were good based on patients perceptions. Profesionalism, problem solving and self direction were in good category also. Meanwhile, most patients said that communication ability was less good. Chi square test proved that there was a relationship between soft skill with nurse caring. There were three soft skill abilities that had relationship with nurse caring, they were communication, professionalism and problem solving. Meanwhile, self direction didn’t have relationship with nurse caring. It was concluded that nurse caring was influenced by their soft skill ability. Chief nurse should supervise the nurse continuously so that they could increase their soft skill ability. Head nurse should make a policy to evaluate nurse soft skill when their performance was measured.